Crohn's and Colitis Canada's 2021 Impact of COVID-19 and Inflammatory Bowel Disease in Canada: Mental Health and Quality of Life. (5th November 2021) - Graff, Lesley A; Fowler, Sharyle; Jones, Jennifer L; Benchimol, Eric I; Bitton, Alain; Huang, James Guoxian; Kuenzig, M Ellen; Kaplan, Gilaad G; Lee, Kate; Mukhtar, Mariam S; Tandon, Parul; Targownik, Laura E; et al.
Abstract: There has been a dramatic rise in mental health difficulties during the coronavirus disease 2019 (COVID-19) pandemic. While young adults have the lowest risk of hospitalization and mortality due to COVID-19, they have been identified as being at highest risk of detrimental mental health outcomes during the pandemic, along with women, those with lower socioeconomic status and those with pre-existing mental health conditions. Somewhat of a crisis in mental health has emerged across the general population through the evolution of the pandemic. A national Canadian survey identified a quadrupling of those experiencing pervasive elevated anxiety symptoms early in the pandemic compared to pre-pandemic levels, and a doubling of those with pervasive elevated depressive symptoms. Independent of the pandemic, persons with inflammatory bowel disease (IBD) can face multiple challenges related to their disease, which can result in a significant psychosocial burden and psychologic distress. Anxiety and depression have been found to be more prevalent in persons with IBD. Many potential factors contribute to the increased psychologic distress and negative impacts on mental health of the COVID-19 pandemic on persons with IBD. These include the fears of contracting COVID-19 or infecting other people. Many believe that IBD or its treatments predispose them to an increased risk of COVID-19 or a worse outcome if acquired. Concerns about access to health care add to mental distress. People with IBD generally report lower quality of life (QOL) compared to community controls. Psychologic interventions, in addition to adequate disease control, have been shown to improve health-related QOL. Uncertainty is another factor associated with reduced health-related QOL. Most studies suggest that persons with IBD have suffered QOL impairment during the pandemic in comparison to the pre-pandemic period. Uncertainties brought on by the pandemic are important contributors for some of the reduction in QOL.